France : Report on the Observance of Standards and Codes (ROSC)-Data Module. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
The report on the Observance of Standards and Codes (ROSC) data module provides a review of France's data dissemination practices against the International Monetary Fund's (IMF) Special Data Dissemination Standard (SDDS), complemented by an in-depth assessment of the quality of six sets of macroeconomic statistics: national accounts, consumer price and producer price indices, government finance statistics, monetary statistics, and balance of payments statistics. Then, it presents recommendations to achieve improvements in the framework. Serviceability focuses on aspects of datasets, and accessibility deals with the availability of information to users.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet